Determination of antioxidant activity and safety of cleansing foam with ultrasonic extract of portulaca oleracea (Portulaca oleracea L.) - Myrzasheva, A.R.; Abdullabekova, R.M.; Urazgaliyev, K.Sh.; Tleubayeva, M.I. (Fundamental and Experimental Biology, 2024)
Currently, the number of cosmeceutical skin care products produced from vegetable raw materials is growing. When exposed to sunlight, free radicals are formed in the skin, which lead to inflammatory reactions at the level of the epidermis and dermis, respectively. To solve this problem, cosmeceuticals that have an antioxidant effect on the skin come to the rescue. The antioxidant activity of the cleansing foam with ultrasonic extract of Portulaca oleracea L. was determined using a DPPH radical removal test, the total amount of polyphenols and flavonoids was determined by spectrophotometric method, the safety and cytotoxic activity of the cleansing foam were determined by HaCaT cells (in vitro). According to the results, it was found that the antioxidant activity of the cleansing foam with ultrasonic extract of Portulaca oleracea L. is 89.1± 0.54, and cell viability is 95 %.